Reduction of Linear Equation in Different Forms

Subject: Optional Mathematics

Find Your Query

Overview

An equation between any two variables which straight line on a graph is known as a linear equation. In this equation, Ax + By + C = 0, where A, B, and C are neutrals and also A and B will not be together zero. This note gives the information about the standard forms of reducing general equation and to find a straight line from the perpendicular length.

Reduction of Linear Equation in Different Forms

Linear Equation Ax + By + C = 0

Linear Equation
Linear Equation
Source:nordenergi.org

An equation between any two variables which straight line on a graph is known as a linear equation. In this equation, Ax + By + C = 0, where A, B, and C are neutrals and also A and B will not be together zero.
To prove this statement, let P(x1, y1), Q(x2, y2) and R(x3, y3) be nay three points on the locus represent by the equation Ax + By + C = 0. The coordinates of the points must satisfy the equation.
Hence,
Ax1 + By1 + C = 0 . . . . . . . . . . . . . . (i)
Ax2 + By2 + C = 0 . . . . . . . . . . . . . . (ii)
Ax3 + By3 + C = 0 . . . . . . . . . . . . . . (iii)
Solving first two equations by the rule of cross multiplication, we get
\(\frac{A}{y_1 - y_2}\) = \(\frac{B}{x_1 - x_2}\) = \(\frac{C}{x_1 y_2 - x_2 y_1}\) = k (say)
∴ A = k(y1 - y2), B = k(x2 - x1) and C = k(x1y2 - x2y1)
Substituting the values of A, B and C in the third equation, we get
k(y1 - y2) x3 +k(x2 - x1) y3 + k(x1y2 - x2y1) = 0
or, k(x3y1 - x3y2 + x2y3 - x1y3 + x1y2 - x2y1) = 0
or, x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3 = 0
Multiplying both sides by \(\frac{1}{2}\), we get
\(\frac{1}{2}\)(x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3) = 0
i.e. Area of ΔPQR = 0
This result sgows us that the points P, Q and R are collinear.
Thus, the general equation of first degree in x and y always represents a straight line.

Scholarships after +2 Abroad Studies Opportunities

Reduction of general equation of first degree to the three standard forms

There is three standard form to reduce the linear equation. They are given below:

Reduction to the slope intercept form
The first-degree general equation in x and y is
Ax + By + C = 0
This equation can be writtenas
By = -Ax - C
or, y = (-\(\frac{A}{B}\))x + (-\(\frac{C}{B}\)) which is of the form y = mx + c where
slope (m) = -\(\frac{A}{B}\) = -\(\frac{coefficient \: of \: x}{coefficient \: of \: y}\) and
Y-intercept (c) = -\(\frac{C}{B}\) = -\(\frac{content \: term}{coefficient \: of \: B}\)

Reduction of the double intercept form
The first-degree general equation in x and y is
Ax + By + C = 0
This equation can be writtenas
Ax + By = -C
Dividing both sides by -C, we get
\(\frac{Ax}{-C}\) + \(\frac{By }{-C}\) = 1
or, \(\frac{x}{\frac{-C}{A}}\) + \(\frac{y}{\frac{-C}{B}}\)= 1 which is of the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1 where
X-interccept (a) = -\(\frac{C}{A}\) = -\(\frac{constant \: term}{coefficient \: of \: x}\)
Y-intercept (b) = -\(\frac{C}{B}\) = -\(\frac{constant \: term}{coefficient \: of \: y}\)

Reduction to the normal form
The equation Ax + By + C = 0 and x cosα = p will represent one and ssame straight line if their corresponding coefficients are proportional.
∴ \(\frac{cosα}{A}\) = \(\frac{sinα}{B}\) = \(\frac{-p}{C}\) = k (say)
Then, cosα = Ak, sinα = Bk and -p = Ck
Now,
(Ak)2 + (Bk)2 = cos2α + sin2α = 1
or, k2 (A2 + B2) = 1
or, k= \(\frac{1}{A^2 + B^2}\)
or, k = ± \(\frac{1}{\sqrt{A^2 + B^2}}\)
∴ cosα = \(\frac{A}{±\sqrt{A^2 + B^2}}\), sinα = \(\frac{B}{±\sqrt{A^2 + B^2}}\) and p = \(\frac{-C}{±\sqrt{A^2 + B^2}}\)
Hence, the normal form is \(\frac{A}{±\sqrt{A^2 + B^2}}\)x + \(\frac{B}{±\sqrt{A^2 + B^2}}\)y = \(\frac{-C}{±\sqrt{A^2 + B^2}}\)
The + or - sign in the RHS being so chosen as to make the RHS positive.

Length of the perpendicular from a point on a straight line

To find the length of the perpendicular from a point on the line x cosα + y sinα = p


Let the equation of a line AB be x cosα + y sinα = p.
Then the length of a perpendicular from the origin on the line is p.
i.e. ON = p and∠AON =α
Let P(x1, y1) be any point and draw perpendicular PM from P to the line AB.
Through the point P, draw a line CD parallel to the given line AB. Let ON' be the perpendicular drawn from the origin to the CD such that ON' = p'.
Then,
PM = ON' - ON' = p' - p when p' > p and PM = ON - ON' = p - p' when p> p'.
Thus, PM = ± (p' - p). Here, the proper sign is taken so as make PM positive.
Now equation of CD is x cosα + y sinα = p'
But this line passes through the point (x1, x1)
So, x1 cosα + y1 sinα = p'
Hence, PM = ± (x1 cosα + y1 sinα - p) which is the length of the perpendicular drawn from (x1, y1) on the line x cosα + y sinα = p.

To find the length of the perpendicular from a point on the line Ax + By + C = 0
Here, the general equation of the first degree in x and y in Ax + By + C = 0.
Changing the equation into perpendicular form we get,
\(\frac{A}{\sqrt{A^2 + B^2}}\)x + \(\frac{B}{\sqrt{A^2 + B^2}}\)y + \(\frac{C}{\sqrt{A^2 + B^2}}\) = 0
Comparing this equation with x cosα + y sinα - p = 0 we get,
cosα = \(\frac{A}{\sqrt{A^2 + B^2}}\), sinα =\(\frac{B}{\sqrt{A^2 + B^2}}\) and p = -\(\frac{C}{\sqrt{A^2 + B^2}}\)
Now, length of the perpendicular drawn from the point (x1, y1) to the line x cosα + y sinα - p is

L = ± (x1 cosα +y1 sinα - p)

= ± (x1\(\frac{A}{\sqrt{A^2 + B^2}}\) + y1\(\frac{B}{\sqrt{A^2 + B^2}}\) -\(\frac{C}{\sqrt{A^2 + B^2}}\))

= ± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))

Hence, length of the perpendicular drawn from the point (x1, y1) to the line
Ax + By + C = 0 is ± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))

 

Things to remember
  1. An equation between any two variables which straight line on a graph is known as a linear equation. In this equation, Ax + By + C = 0, where A, B, and C are neutrals and also A and B will not be together zero.
  2. Ax + By + C = 0 is± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))
  3. Ax + By + C = 0
  4. \(\frac{1}{2}\)(x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3) = 0
  • It includes every relationship which established among the people.
  • There can be more than one community in a society. Community smaller than society.
  • It is a network of social relationships which cannot see or touched.
  • common interests and common objectives are not necessary for society.
Videos for Reduction of Linear Equation in Different Forms
Algebra: Solving Linear Equations
Graphing Linear Equations
Solving Linear Equations Made Easy!
Questions and Answers

Solution:

Here, 
3x + 4y + 5 = 0 
Reduce it into slope intercept from, 4y = -3x - 5 
or, y = \(\frac{-3}{4}\) x - \(\frac{5}{4}\)
which is in the form y = mx + c, 
so, on comparing, we get,
Slope (m) = \(\frac{-3}{4}\) and 
y-intercept (c) = \(\frac{-5}{4}\)

Solution:

Here, 
4x + 5y + 20 = 0 
or, \(\frac{4x}{-20}\) + \(\frac{5y}{-20}\) = 1
or, \(\frac{x}{-20/4}\) + \(\frac{y}{-20/5}\)
or, \(\frac{x}{-5}\) + \(\frac{y}{-4}\) = 1 
which is in the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1,
∴ x-intercept (a) = -5 and y-intercept (b) = -4

Solution:

x - \(\sqrt{3}\) y - 6 = 0
or, x - \(\sqrt{3}\) y = 6
Now, 
= \(\sqrt{(coefficient \: of \: x)^2 + (coefficient \: of \: y)^2}\)
= \(\sqrt{(1)^2 + (-\sqrt{3})^2}\)
= \(\sqrt{1 + 3}\) 
= \(\sqrt{4}\) 
= 2.

Dividing both sides by 2, we get,
\(\frac{1}{2}\) x - \(\frac{\sqrt{3}}{2}\) y = \(\frac{6}{2}\) 
or, \(\frac{1}{2}\) x + (\(\frac{\sqrt{3}}{2}\)) y = 3
which is in form x cosα + y sinα = p
∴p = 3 units, cosα = \(\frac{1}{2}\) and sinα = -\(\frac{\sqrt{3}}{2}\)
Since, cosα is positive and sinα = -\(\frac{\sqrt{3}}{2}\), α lies in the 4th quardrant.
∴ cosα = \(\frac{1}{2}\) 
cosα = cosα (360° - 60°) 
α = 300° 
∴ x cos 300° + y sin 300° = 3

Solution:

Here, 
2x + 5y - 20 = 0 
or, 2x + 5y = 20 
or, \(\frac{2x}{20}\) + \(\frac{5y}{20}\) = 1 
or, \(\frac{x}{10}\) + \(\frac{y}{4}\) = 1 
Which is in the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1
∴ X-intercept (a) = 10
y-intercept (b) = 4 
∴ Area of ΔAOB = \(\frac{1}{2}\) OA × OB 
= \(\frac{1}{2}\) × 10 × 4 
= 20 sq. units

Solution:

The equation of line is 3x + 4y + 7 = 0 
Perpendicular length (p) = |\(\frac{ax_1 + by_1 + c}{\sqrt{a^2 + b^2}}\)|

we have, (x1,y1)= (-3,0)

So, p =  |\(\frac{3\times(-3)+ 4\times 0}{\sqrt{3^2 + 4^2}}\)|= \(\frac{9}{5}\)

Solution:

The equation of line is 3x + 4y + 7 = 0 
Perpendicular length (p) =\(\vert \frac{ax_1+by_1+c}{\sqrt{a^2+b^2}}\vert\)
Where (x1 , y1) is the point from whhich the perpendicular is drawn on the line 
or, p = \(\vert\frac{3 . (-3) + 4 . 0 + 7}{\sqrt{(3)^2 + (4)^2}}\vert\)
or, p = \(\vert\frac{-9 + 7}{\sqrt{9 + 16}}\vert\)
or, p = \(\vert\frac{-2}{5}\vert\)
∴ p = \(\frac{2}{5}\) units

Solution:

Here,
Let \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1 be the equation of a line peprendicular length frawn from origin (0, 0) to \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1 and its equation is given by 
or, p = \(\vert\frac{0 . \frac{1}{a} + 0 . \frac{1}{b} - 1}{\sqrt{\frac{1}{a^2} + \frac{1}{b^2}}}\vert\)
or, p = \(\frac{1}{\sqrt{\frac{1}{a^2} + \frac{1}{b^2}}}\)
Squaring on both sides we get,
or, p2 = \(\frac{1}{\frac{1}{a^2} + \frac{1}{b^2}}\)
or, \(\frac{1}{a^2}\) + \(\frac{1}{b^2}\) = \(\frac{1}{p^2}\)
∴ \(\frac{1}{p^2}\) = \(\frac{1}{a^2}\) + \(\frac{1}{b^2}\) proved.

Quiz

© 2019-20 Kullabs. All Rights Reserved.